Competitive binding of viral E2 protein and mammalian core-binding factor to transcriptional control sequences of human papillomavirus type 8 and bovine papillomavirus type 1. - Schmidt, H M (1997)
The promoter P7535 of human papillomavirus type 8 and the promoter P7185 of bovine papillomavirus type 1 are negatively regulated by viral E2 proteins via the promoter proximal binding sites P2 and BS1, respectively. Mutations of these E2 binding sites can reduce basal promoter activity. This suggests binding of a transcription-stimulating factor and may indicate that repression by E2 is due to competitive binding of viral and cellular proteins. A computer search revealed putative binding sites for core-binding factor (CBF; also referred to as PEA2, PEBP2, or AML), overlapping with P2 and BS1. Binding of recombinant CBF proteins to these sites was confirmed by band shift analysis. Competition of CBF and E2 protein for DNA binding was shown for both human papillomavirus type 8 and bovine papillomavirus type 1. The importance of CBF-E2 competition in E2-mediated repression could be demonstrated by comparing the E2 effect on P7185 activity in two cell lines containing different amounts of endogenous CBF. In cells with large amounts of CBF, E2 repressed P7185 wild-type constructs to the basal promoter activity of a mutant (50%) that could not bind this protein any more. In contrast, in a cell line containing small amounts of CBF, the promoter activities of constructs with wild-type and mutated CBF binding sites hardly differed and specific repression by E2 was not detectable.